DETERMINANT OF INTEGRATED REPORTING AND GREEN INNOVATION ON EARNINGS QUALITY - Etty Murwaningsari; Sahreza Harahap (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This research is to examine (1) The effect of integrated reporting and green innovation on earnings quality. (2) The frequency of board meetings moderates the positive influence of integrated reporting and green innovation on earnings quality. The results of this research state that there is a significant positive influence of integrated reporting on earnings quality, where green innovation does not have a significant influence on earnings quality. And the frequency of board meetings strengthens the positive influence of integrated reporting on earnings quality. The contribution of the research is to the development of integrated reporting and green innovation studies in companies listed on the Indonesian Stock Exchange